2022
DOI: 10.3390/su14148934
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of EFL Teachers’ Technological Pedagogical Content Knowledge (TPACK) Situated in Multiple Learning Activity Systems

Abstract: This study examined how Chinese college teachers developed their Technological Pedagogical Content Knowledge (TPACK) by situating the learning process in three interactive activity systems during teaching English as foreign language (EFL) online in China. Data were collected from teachers’ diaries, in-depth interviews, and various records of online teaching. Findings indicated that teachers employed cultural artifacts, social relations, and beliefs and concepts to cope with difficulties that confronted their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The AI-TPACK model equips teachers to modify their pedagogical approaches to include AI, thereby preparing students with essential skills for a digitally driven society. This approach is not only innovative but also addresses the dynamic educational needs of a technology-centric world, contributing to the sustainability of educational practices [102].…”
Section: Discussionmentioning
confidence: 99%
“…The AI-TPACK model equips teachers to modify their pedagogical approaches to include AI, thereby preparing students with essential skills for a digitally driven society. This approach is not only innovative but also addresses the dynamic educational needs of a technology-centric world, contributing to the sustainability of educational practices [102].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted to assess the teachers learning through the online teaching, which showed that teachers were not able to perform, and it was difficult for them in online engagement. Technological Pedagogical Content Knowledge (TPACK) model proposed and studied for the justification on the importance of contents in textbooks as an essential part for the professional development of teachers [36]. The model provides three bases for knowledge as Technology Knowledge (TK), Content Knowledge (CK), and Pedagogical Knowledge (PK) consisting of seven components (Figure 3).…”
Section: The Role Of Textbooks In Teaching and Learningmentioning
confidence: 99%
“…Implementing L2 ecological pedagogy through reflective teaching encourages teachers to pursue CPD in aspects such as innovation in the classroom [ 99 , 100 ], identity commitment [ 101 , 102 ], and social and cultural wellness [ 103 , 104 ]. Teacher agency was the focus of inquiries under frameworks such as activity system and sociocultural theory [ 105 , 106 ]. A majority of studies examined teachers’ articulated agency in retrospective interviews [ 95 , 107 , 108 ], whereas actual alternation of agency in response to affordance changes in the classroom were less investigated [ 109 , 110 ].…”
Section: Introductionmentioning
confidence: 99%